Reestructuración económica y desigualdades interregionales. El caso de Chile - Uribe-Echevarría, Francisco (Revista EURE - Revista de Estudios Urbano Regionales, 1996)
This document analyses the evolution of the patterns of regional development in Chile in the last three decades. Its main purpose is to identify the impact of the new environment of public policies about these patterns, as a complement, it is also proposed to advance in the formulation of explanatory hypothesis for the observed phenomena. The analysis is centred on the last fifteen years, when the impact of these reformations begins to be visible and it focuses on the inter-regional dimension of the social and economic differences. Having adopted this decision implies leaving for other occasion an advance, very necessary of course, in the field of inter-regional inequialities. The document has been organized in three main sections. The first one analyses, after a brief examination on the trends of the territorial concentration, the empiric evidence about the evolution of the inter-regional inequalities. The second section sketches, from the examination on the main transformation occurred in the country, some explanatory hypothesis about the observed evolution. In this analysis, they started from the changes in the section structures of national Economy and then to explore the evolution of the section productiveness and the concerning of the new approach about social policies. Finally, the third section uses the conclusions of the two previous sections for an interpretative and conceptualization effort that includes some reflections about the future prospective of the Chilean process and its implications on the public policies from the point of view of the regional realities.